Man-Machine Interactions 6 : 6th International Conference on Man-Machine Interactions, ICMMI 2019, Cracow, Poland, October 2-3 2019 /: 6th International Conference on Man-Machine Interactions, ICMMI 2019, Cracow, Poland, October 2-3 2019. (©2020) - Unknown
No abstract available